Again on the Leopardi’s trace in the political discourse of the passion in Italy. - Martínez Garrido, Elisa (Cuadernos de Filología Italiana, 2003)
This paper tries to correlate the first two canzoni of Leopardi with some great texts of the italian literary tradition, inside the pragmatics and literary rhetoric, that form what has been denominated political speech of passion in Italy.